Model Design for The Implementation of Innovative Methods in Companies in The Food Industry According to Size Category - Milan MAJERNÍK; Stefan MAJERNIK (Communications of International Proceedings, 2022)
Today, information and knowledge create a ranking of the most developed countries and economies, transferred through their productivity and performance. By analogy, the new economy today is a flow of innovation and adaptation. It is an economy of innovation, information and new ideas that become a commodity and are reflected in all sectors as well as in the food industry. The purpose of the research presented in the article is the implementation of innovative technologies for processing food products corresponding to research and technical development. The main result is a model design based on SWOT analysis in the implementation of innovative methods in companies in the food industry according to their size category. The findings of the economic aspects of innovation potential as competitiveness are also applicable in the food industry.
Keywords: Global Innovation Index; innovation methods; technical development; SWOT analysis; food industry.